An Empirical Study of IPOs Underpricing on China A-Share Market and Hong Kong Main Board Exchange - Wang, Zhixuan (2010)
The paper investigates the phenomenon of Initial Public Offerings underpricing on China Mainland A-share market and Hong Kong Exchange Main board by using sample of 61 and 66 new issues respectively, from 1 January 2009 to 31 December 2009. Firstly, the initial returns are examined and analyzed across the two markets. Along with the first day return, the short-term performance of IPOs within the two markets is evaluated. The statistics show that first day returns in China A-Share market are significantly higher than the returns in the Hong Kong Exchange. However, investors who hold shares in Hong Kong from the first trading day of the IPO until a 6- month period perform considerably better than holding shares in of the same timeframe in A-Share market. Furthermore, several variables influencing the level of underpricing are inferred from the hypotheses based on the information asymmetry theory. The results indicate that the variables derived from the classical information asymmetry theory, involving winner’s curse, ex ante uncertainty and signaling model can partly explain the phenomenon of underpricing for both two markets.